Effect of zeolite (in feed) on growth performances of red tilapia (Oreochromis sp.) - Mohd Noor, Norfakhrina (2012)
The effect of zeolite added in diet of Oreochromis sp. was investigated in the present study. Zeolite was added in the diet at varying level, 0% (T1), 0.5% (T2), 1.0% (T3) and 1.5% (T4) and fed to fish for 12 weeks. Growth performance of the Oreochromis sp. was observed in term of weight gain, body length, specific growth rate, food conversion ratio and survival rate. Proximate analyses were also conducted at the end of the study to compare the body composition of the fish among treatments. The results of the study showed that the average body weights of fish in the treatments T1, T2, T3 and T4 were 40.36±17.51 g, 34.09±16.78 g, 40.07±18.61 g, 38.66±18.42 g respectively and similarly average total lengths were 12.44±1.82 cm, 12.12±2.63 cm, 12.57±2.30 cm, 12.37±2.29 cm respectively. However, there was no statistical difference among treatments for all parameters of growth performance (P>0.05). The body composition showed there were statistical different (P<0.05) on protein, lipid and ash among treatments. T1 (55.68±1.44%) showed the highest percentage of protein followed by T3 (55.46±0.77%), T4 (55.19±1.12%) and T2 (53.31±0.7%). Thus, this study showed the growth rates of Oreochromis sp. were not affected by different concentrations of zeolite in feed.